2013
DOI: 10.1152/ajpregu.00128.2013
|View full text |Cite
|
Sign up to set email alerts
|

Human inflammatory and resolving lipid mediator responses to resistance exercise and ibuprofen treatment

Abstract: Classical proinflammatory eicosanoids, and more recently discovered lipid mediators with anti-inflammatory and proresolving bioactivity, exert a complex role in the initiation, control, and resolution of inflammation. Using a targeted lipidomics approach, we investigated circulating lipid mediator responses to resistance exercise and treatment with the NSAID ibuprofen. Human subjects undertook a single bout of unaccustomed resistance exercise (80% of one repetition maximum) following oral ingestion of ibuprofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
158
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(195 citation statements)
references
References 108 publications
25
158
3
1
Order By: Relevance
“…The amounts of SPMs detected in this study would equate to low-mid nanomolar tissue concentrations, which are biologically significant. SPMs and their precursors have also previously been detected in normal human plasma and lymphoid organs (Mas et al 2012, Markworth et al 2013, Colas et al 2014 and in human milk (Weiss et al 2013). Similar to our studies, markedly higher concentrations of the primary Rv precursors, 17-HDHA and 18-HEPE, were detected in these studies compared with their downstream products.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The amounts of SPMs detected in this study would equate to low-mid nanomolar tissue concentrations, which are biologically significant. SPMs and their precursors have also previously been detected in normal human plasma and lymphoid organs (Mas et al 2012, Markworth et al 2013, Colas et al 2014 and in human milk (Weiss et al 2013). Similar to our studies, markedly higher concentrations of the primary Rv precursors, 17-HDHA and 18-HEPE, were detected in these studies compared with their downstream products.…”
Section: Discussionsupporting
confidence: 91%
“…Circulating SPMs have been measured in healthy subjects (Mas et al 2012), with concentrations shown to be associated with n-3 PUFA intake (Colas et al 2014) and produced in greater amounts after exercise in patients taking ibuprofen (Markworth et al 2013). SPMs have been measured in breast milk (Weiss et al 2013), but to date have not been investigated in the context of human pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of this stems from studies showing that the nonsteroidal anti-inflammatory drugs disrupt both the early translational responses within skeletal muscle 23 and the resolving lipid mediator response. 24 A dynamic, time-dependent polarization of macrophages during the tissue repair process further exemplifies the importance of the initial inflammatory response to exercise. A switch from an initial M1 proinflammatory phenotype 24 h after eccentric exercise, to an M2, antiinflammatory phenotype 48-72-h after exercise, characterizes this phenomenon.…”
Section: The Resolution Of Inflammation Within Skeletal Muscle: a Coomentioning
confidence: 98%
“…Little information has been published on the influence of exercise on plasma 13-HODE ϩ 9-HODE, and whether postexercise increases relate to changes in established biomarkers of oxidative stress and inflammation (19,20). Using a metabolomics approach, we recently reported that plasma 13-HODE ϩ 9-HODE increased 5.5-fold in 15 runners following a 3-day period of intensified training (2.5 h/day running at 70% V O 2max ), with levels returning to preexercise levels after 14-h recovery (20).…”
mentioning
confidence: 99%